How Telemedicine Help People To Feel Secure During Pandemic of Covid-19 - Rika Fitriyana (Asian Social Work Journal, 2022)
The aim of this paper is to give brief explanation about how the world changed after covid-19 outbreak. Thus situation forced people to adapt in order to survive this ongoing stressful life event. Almost all country in the world began to apply social distancing policy just to protect people from the risk of getting exposed by the virus. As the result, people are getting hard to reach health facility when they need it. Day by day, the numbers of active cases keep increasing and getting hard to control. Health is one of important thing in human’s life. Because if they don’t take good care of their health, then something bad might happen. Indonesian government through The Ministry of Health created new regulation about telemedicine in order to give alternative in solving health problems for those who is unwilling to leave the house or visiting the nearest public health facility. Of course there will always be pros and cons but as scientist, we should learn to see things objectively. That’s why in this paper, we will discuss further about how this service helps many people’s life and bring security in so-called “new normal” or others may say “life after pandemic”.